SPRAWIEDLIWOŚĆ SPOŁECZNA W ŚWIETLE ENCYKLIKI DEUS CARITAS EST BENEDYKTA XVI - Stołpiec, Katarzyna (Studia Pastoralne, 2023)
The article presents an historical section of the rising and application the idea of the social justice in the social education, beginning from ideas of ancient philosophers leading to presence in nowadays teaching of Catholic church. The considerations was based on the encyclical Deus caritas est of the pope Benedict XVI being a fundamental source showing the justice as a virtue which fool of its progress is achieved in love.